Mechanical and tribological behaviors of copper metal matrix composites for brake pads used in high-speed trains. (March 2018) - Xiao, Yelong; Zhang, Zhongyi; Yao, Pingping; Fan, Kunyang; Zhou, Haibin; Gong, Taimin; Zhao, Lin; Deng, Minwen
Abstract: As one of the most important components in high-speed trains, demands are improved on the mechanical and tribological properties of materials for brake pads. In this study, a newly developed copper metal matrix composite (Cu-MMC) for the aforementioned brake pads was fabricated by powder metallurgy route. The microstructure and mechanical properties of Cu-MMC were investigated. Cu-MMC was tribo-evaluated by a full-scale dynamometer, and special attention was paid on the braking performances during emergency stop-braking at initial speeds from 300 to 380 km/h. Examination and analysis of the worn surface and subsurface corroborated the wear mechanism. The results indicate that Cu-MMC exhibits excellent properties and can meet the technical requirements, so it holds great promise for applications in high-speed trains. Highlights: A newly developed copper metal matrix composite for high-speed trains was fabricated by powder metallurgy route. The braking tests were conducted on a full-scale dynamometer designed to simulate brake characteristics of high-speed trains. Compared with materials in service, Cu-MMC exhibited superior mechanical and tribological properties. The worn surface and subsurface were characterised by SEM and EDS.